Investigation on aluminium/mild steel plates bonded polyurethane sheets to control vibration. (2021) - Vijayakumar, K.R.; Jayaseelan, J.; Ethiraj, N.; Prabhahar, M.; Bhaskar, K.; Jayabalakrishnan, D.; Sendilvelan, S.; Krishnamoorthi, Sangeetha
Abstract: In the present work aluminium and mild steel plates bonded polyurethane (PU) sheet specimens are used to investigate extension damping properties and fracture toughness. Vibration testing reveals the rapid features (frequencies occurred naturally, shapes of mode and damping) for the structures which gives an insight to the behavior of the structure under its operating conditions. This dynamic characterization helps in design modification of the structures to a fail proof design. Near the resonance frequencies the structures get to vibrate with higher amplitudes which may lead to the structural failure. To avoid this, the structural vibrations need to be controlled. In the present study passive damping technique has been employed to control the structural vibrations. Polyurethane (PU) sheets as damping material is used to apply on to the structures under consideration for the damping evaluation studies and experiments were done to evaluate the performance of the damping material. In the present study the effectiveness of passive damping technique using PU material for control of vibrations is explored and the vibration responses are analysed. From the vibration analysis it is observed that PU aluminium is better than mild streel. Also, from frequency response function it is observed that there is improvement in damping from 200 Hz onwards.